Compromise Approach as a Model of Social Conflict Intervention (Case Study in Kumbe Village, Rasanae Timur District, Bima City) - Hendra, Hendra; Taufiq, Muhammad; Rusli, Rusli; Rijal, Muhammad Nur; Budiman, Arif; Rizkiani, Firliah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Social conflict is an inevitable aspect of community life, which, if not properly managed, can result in social, economic, and psychological losses. This study aims to analyze the implementation of the compromise approach as an intervention model for resolving social conflicts in Kumbe Village, Rasanae Timur District, Bima City. The research employed a qualitative descriptive approach with a case study method, involving informants from community leaders, village officials, police officers, mediators, conflict actors, and affected residents. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman model, with validity ensured through triangulation and member checking. The findings indicate that the Head of Kumbe Village consistently applied two conflict resolution styles: accommodation and compromise. The accommodation style is characterized by cooperation, openness to input, providing space for other parties, and maintaining harmony, which fosters a peaceful atmosphere and reduces tension. The compromise style is implemented through a give-and-take principle, emphasis on common ground, temporary resolutions in urgent situations, and practical decision-making, allowing conflicts to be resolved quickly, fairly, and acceptably to all parties. This study confirms that the compromise approach serves as an effective intervention model for managing social conflicts at the village level.